Syukur sebagai Pencegah Insecure Perspektif Abu Hamid Al-Ghazali - Hakim, Lukman; Baaly, Ali Sajjad; Yamani, Abu Bakar (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2024)
In the contemporary era characterized by rapid technological advancements, humans encounter both conveniences and challenges, one of which is the emergence of feelings of insecurity. This study aims to explore the feeling of insecurity and its relationship with the concept of gratitude within Sufism, from the perspective of Abu Hamid Al-Ghazali, as a preventative strategy. Employing a qualitative methodology with a descriptive-analytical approach, this research reveals that gratitude can serve as an effective mechanism to mitigate feelings of insecurity. According to Al-Ghazali, gratitude comprises three hierarchical components: knowledge, spiritual state, and action. The findings indicate that the internalization and practice of these components can act as preventative measures against insecurity. In terms of knowledge, individuals are required to acknowledge and believe that everything originates from Allah, which stimulates positive thinking and happiness towards Allah and oneself. This belief and love for Allah lead to an intrinsic desire to perform good deeds, indirectly alleviating feelings of insecurity.Abstrak: Di era modern yang ditandai dengan pesatnya perkembangan teknologi, manusia menghadapi berbagai kemudahan sekaligus tantangan, salah satunya adalah munculnya perasaan tidak aman atau insecure. Penelitian ini bertujuan untuk mengkaji perasaan insecure dan hubungannya dengan konsep syukur dalam sufisme, berdasarkan perspektif Abu Hamid Al-Ghazali, sebagai strategi preventif. Menggunakan metodologi kualitatif dengan pendekatan deskriptif-analitis, studi ini mengungkapkan bahwa syukur dapat menjadi mekanisme efektif untuk mengatasi perasaan insecure. Menurut Al-Ghazali, syukur terdiri dari tiga komponen hierarkis: pengetahuan (ilmu), kondisi spiritual (hal), dan tindakan (amal). Penelitian ini menunjukkan bahwa proses internalisasi dan praktik dari ketiga komponen ini dapat berfungsi sebagai langkah preventif terhadap insecure. Dalam aspek ilmu, diwajibkan bagi individu untuk mengakui dan percaya bahwa segala sesuatu berasal dari Allah, yang menstimulasi pemikiran positif dan rasa bahagia terhadap Allah dan diri sendiri. Kepercayaan dan cinta kepada Allah mengarah pada keinginan intrinsik untuk berbuat baik, secara tidak langsung menekan perasaan insecure.